Studying childhood and early childhood: a guide for students - Sambell, Kay; Miller, Sue; Gibson, Mel (London, 2005)
The book is designed to provide students studying the course in higher education with the means to do better, to be more successful and to work towards achieving the learning outcomes with greater confidence.
Keywords: Child Development; Child Welfare; Children-Services; Early Childhood Education